Strategi Literasi Visual dalam Meningkatkan Kemampuan Membaca Anak Usia Dini Melalui Buku Bergambar - Dewi Kartika Zaing (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to describe visual literacy strategies through picture books in improving early childhood reading skills. This research used a descriptive qualitative approach involving teachers and children aged 5–6 years at an Early Childhood Education institution. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that picture books effectively increased children’s reading interest, letter recognition ability, vocabulary comprehension, and communication skills. Teachers implemented shared reading, picture observation, and question-and-answer strategies to create interactive and enjoyable learning activities. The novelty of this study lies in the integration of visual literacy strategies through interactive picture books to support children’s early reading development in classroom learning activities. The study implies that picture books can become effective literacy media for developing language skills and active participation among early childhood learners.